Impact of Long Run Exposure to Television on Homicides : Some Evidence from Brazil - Chong, Alberto; Yañez-Pagans, Mónica (Taylor and Francis, 2016)
This paper focuses on the link between television coverage and violent crime, in particular, homicides in Brazil, a country where crime has grown dramatically in recent decades. Using Census data for the period 1980–2000, the paper finds that people living in areas covered by television signal have significantly lower rates of homicides. The effect is strongest for men of lower socioeconomic status.